Do We Have Normative Powers?. (1st July 2020) - Chang, Ruth
Abstract: 'Normative powers' are capacities to create normative reasons by our willing or say-so. They are significant, because if we have them and exercise them, then sometimes the reasons we have are 'up to us'. But such powers seem mysterious. How can we, by willing, create reasons? In this paper, I examine whether normative powers can be adequately explained normatively, by appeal to norms of a practice, normative principles, human interests, or values. Can normative explanations of normative powers explain how an exercise of the will can afford us special freedom in determining our reasons? I argue that normative approaches to answering this question prove to be inadequate. To vindicate the thought that normative powers can make our reasons 'up to us', we need an altogether different approach to understanding them, one that is located not in the normative but in the metaphysical. I end the paper by sketching a metaphysical explanation of normative powers. This metaphysical defence of normative powers provides a window into a different, more agent-centered way of thinking about rational agency.